(untitled) (Acta Entomologica Serbica, 2017)
Epitrix hirtipennis (Melsheimer, 1847) causes damage to tobacco plants throughout the growing season. The most severe damages were observed in the first three weeks after tobacco transplanting. It is very difficult for damaged plants to adapt after transplanting, often resulting in their death. The study was conducted in 2013-2014 in several villages in the southeast and Pelagonia region of the Republic of Macedonia, where tobacco is an abundant crop. During 2013, the major attack was registered in June on sand leaves (3212), bottom leaves (2584), and first middle leaves (1905), with the pest population gradually decreasing on second middle leaves (1218), third middle leaves (894), lower top leaves (649) and top leaves (411). The major attacks in 2013 were determined in Budakovo and Desovo. In 2014, the most intense attack of E. hirtipennis was in Konce on sand leaves with an average of 40.86%, and the average in all regions was 35.71%. The percentage of attacked bottom leaves and first middle leaves was on average 10.55%.